Neurodevelopmental effect of intracranial hemorrhage observed in hypoxic ischemic brain injury in hypothermia-treated asphyxiated neonates - an MRI study - Andrea Lakatos; Márton Kolossváry; Miklós Szabó; Ágnes Jermendy; Hajnalka Barta; Gyula Gyebnár; Gábor Rudas; Lajos R. Kozák (BMC, 2019)
Abstract Background Identification of early signs of hypoxic ischemic encephalopathy (HIE) with magnetic resonance imaging (MRI) has proven of prognostic significance. Yet, the importance of intracranial hemorrhage (ICH), being present concomitantly had not been investigated yet, despite the known influence of hypothermia on hemostasis. We aimed to determine whether presence of ICH on MRI alongside the signs of HIE have an impact on prognosis in neonates with the clinical diagnosis of HIE. Methods A retrospective study of consecutively sampled 108 asphyxiated term infants admitted to a tertiary neonatal intensive care unit (between 2007 and 2016), treated with whole body hypothermia and having brain MRI within 1 week of life was conducted. Presence or absence of HIE signs on MRI (basal ganglia-thalamus, watershed pattern and total brain injury) and on MR spectroscopy (lactate peak with decreased normal metabolites measured by Lac/NAA ratio) and/or of the five major types of ICH were recorded. Neurodevelopmental outcome was measured with Bayley Scales of Infant Development-II (BSID-II) test. Death or abnormal neurodevelopment (BSID-II score < 85) was defined as poor outcome in Chi-square test. Multivariate logistic regression analysis was performed on survivors. Results MRI and MR-spectroscopy (MRS) signs of HIE were present in 72% (n = 78). 36% (n = 39) of neonates had ICH, being mainly small in size. Chi-square test showed a relationship between neurodevelopmental outcome and initial MRI. Unadjusted logistic regression showed that neonates presenting MRI and MRS signs of HIE have 6.23 times higher odds for delayed mental development (OR = 6.2292; CI95% = [1.2642; 30.6934], p = 0.0246), than infants without imaging alterations; with no ICH effect on outcome. Adjustment for clinical and imaging parameters did not change the pattern of results, i.e. HIE remained an independent risk factor for delayed neurodevelopment (OR = 6.2496; CI95% = [1.2018; 32.4983], p = 0.0294), while ICH remained to have no significant effect. Conclusion HIE related MRI abnormalities proved to be important prognostic factors of poor outcome in cooled asphyxiated infants when present, suggesting that early MRI with MRS is beneficial for prognostication. Interestingly, ICHs present in about one third of all cases had no significant effect on neurodevelopmental outcome, despite the known hemostasis altering effects of hypothermia.